Nullarbora Ekins & Erpenbeck & Goudie & Hooper 2020, gen. nov. - Ekins, Merrick; Erpenbeck, Dirk; Goudie, Lisa; Hooper, John N. A. (Zenodo, 2020)
Genus Nullarbora gen. nov. urn:lsid:zoobank.org:act: 313FA390-1049-41D6-9CEA-EBFD7B811BCE Type species: Nullarbora heptaxia gen nov. sp. nov. Definition: Cladorhizidae with anchorate anisochelae and a pinnate body shape, i.e. filaments at right angle to a straight stem. Etymology: Nullus L. null, Arbor L. trees. The Nullarbor Plain is also the name of the land surrounding the Great Australian Bight from where the newly discovered species in this manuscript were collected. Species also included: N. acanthoxea (Hestetun, Fourt, Vacelet, Boury-Esnault & Rapp, 2015), N. caillieti (Lundsten, Reiswig & Austin, 2014), N. evae (Lundsten, Reiswig & Austin, 2014), N. fristedtii (Lambe, 1900), N. grimaldii (Topsent, 1909), N. investigator (Ekins, Erpenbeck & Hooper, 2020), N. linearis (Ridley & Dendy, 1887), N. microchela (Lévi, 1964), N. penniformis (Göcke & Janussen, 2013), N. pteron (Reiswig & Lee, 2007), N. rectangularis (Ridley & Dendy, 1886), N. segonzaci (Vacelet, 2006) and N. septemdentalis (Koltun, 1970). : Published as part of Ekins, Merrick, Erpenbeck, Dirk, Goudie, Lisa & Hooper, John N. A., 2020, New carnivorous sponges and allied species from the Great Australian Bight, pp. 240-266 in Zootaxa 4878 (2) on page 244, DOI: 10.11646/zootaxa.4878.2.2, http://zenodo.org/record/4424977 : {"references": ["Hestetun, J., Fourt, M., Vacelet, J., Boury-Esnault, N. & Rapp, H. T. (2015) Cladorhizidae (Porifera, Demospongiae, Poecilosclerida) of the deep Atlantic collected during Ifremer cruises, with a biogeographic overview of the Atlantic species. Journal of the Marine Biological Association of the United Kingdom, 95 (7), 1311 - 1343. https: // doi. org / 10.1017 / S 0025315413001100", "Lundsten, L., Reiswig, H. M. & Austin, W. C. (2014) Four new species of Cladorhizidae (Porifera, Demospongiae, Poecilosclerida) from the Northeast Pacific. Zootaxa, 3786 (2), 101 - 123. https: // doi. org / 10.11646 / zootaxa. 3786.2.1", "Lambe, L. M. (1900) Sponges from the coasts of north-eastern Canada and Greenland. Transactions of the Royal Society of Canada, 6, 19 - 49.", "Topsent, E. (1909) Etude sur quelques Cladorhiza et sur Euchelipluma pristina n. g. et n. sp. Bulletin de l'Institut oceanographique, Monaco, 151, 1 - 23, pls. I-II.", "Ekins, M., Erpenbeck, D. & Hooper, J. N. A. (2020) Carnivorous sponges from the Australian Bathyal and Abyssal zones collected during the RV Investigator 2017 Expedition. Zootaxa, 4774 (1), 1 - 159. https: // doi. org / 10.11646 / zootaxa. 4774.1.1", "Ridley, S. O. & Dendy, A. (1887) Report on the Monaxonida collected by H. M. S. Challenger during the years 1873 - 1876. Report on the Scientific Results of the Voyage of H. M. S. ' Challenger', 1873 - 1876. Zoology, 20 (59), i-lxviii + 1 - 275, pls. I-LI, 1 map.", "Levi, C. (1964) Spongiaires des zones bathyale, abyssale et hadale. Galathea Report. Scientific Results of The Danish Deep-Sea Expedition Round the World, 1950 - 52, 7, 63 - 112.", "Gocke, C. & Janussen, D. (2013) Demospongiae of ANT XXIV / 2 (SYSTCO I) Expedition-Antarctic Eastern Weddell Sea. Zootaxa, 3692 (1), 28 - 101. https: // doi. org / 10.11646 / zootaxa. 3692.1.5", "Reiswig, H. M. & Lee, W. L. (2007) A new species of Cladorhiza (Porifera: Cladorhizidae) from S. California (USA). In: Custodio, M. R., Lobo-Hajdu, G., Hajdu, E. & Muricy, G. (Eds.), Porifera Research. Biodiversity, Innovation and Sustainability. Livros de Museu Nacional 28. Museu Nacional, Rio de Janeiro, pp. 517 - 523.", "Ridley, S. O. & Dendy, A. (1886) Preliminary report on the Monaxonida collected by H. M. S. Challenger. Part I. Annals and Magazine of Natural History, Series 5, 18 (108), 325 - 351, 470 - 493. https: // doi. org / 10.1080 / 00222938609459998", "Vacelet, J. (2006) New carnivorous sponges (Porifera, Poecilosclerida) collected from manned submersibles in the deep Pacific. Zoological Journal of the Linnaean Society, 148, 553 - 584. https: // doi. org / 10.1111 / j. 1096 - 3642.2006.00234. x", "Koltun, V. M. (1970) Sponge fauna of the northwestern Pacific from the shallows to the hadal depths. In: Bogorov, V. G. (Ed.), Fauna of the Kurile-Kamchatka Trench and its environment. Institute of Oceanology of the Academy of Sciences of the U. S. S. R. Vol. 86. Akademiya Nauk SSSR. Trudy Instituta Okeanologii in P. P. Shishov and Izdatelstvo Nauka, Moskwa, pp. 165 - 221."]}